FEASIBILITY STUDY OF DOMESTICATION OF WADER FISH (PUNTIUS BINOTATUS) IN THE BRANTAS WATERSHED AREA, EAST JAVA - Ferawati, Yunetta; Khusaini, Moh.; Parmawati, Rita; Efani, Anthon (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2025)
Puntius binotatus Wader fish in the Brantas River Basin, East Java has an important position for society and the environment, so it is important to make an effort to maintain its sustainability, one of which is through Domestication. This study aims to further examine whether the domestication of Puntius binotatus Wader fish is feasible as an alternative farming business for the community in the Brantas River Basin, East Java. The feasibility analysis of Puntius binotatus Wader fish domestication was carried out by analyzing the market, technical, management, social, and environmental aspects first before conducting a financial analysis. The results of the analysis show that the market share of Wader fish seeds where the demand for seeds is greater than the existing supply. Technically, there are no obstacles or problems that hinder the running of the business. Domestication implementers can run their businesses because they already have a fairly good organizational structure. Social and environmental analysis shows that the Wader Cakul fish seed business (Puntius binotatus) is very feasible to run because it has a positive impact on society and maintains the sustainability of the surrounding natural environment. Financially, the Wader Cakul (Puntius binotatus) fish breeding business at UPT PBAT Umbulan obtained an NPV value greater than zero, which is Rp109,256,722. Net B/C is greater than one, which is 2.35. The IRR value obtained from the financial analysis of the Wader Cakul (Puntius binotatus) fish farming business is 30.16 percent, where the IRR value is greater than the applicable discount rate of 4.75 percent, which means that the Wader Cakul (Puntius binotatus) fish farming business is financially feasible to be implemented